Recovery Pattern of High-Frequency Acceleration Vestibulo-Ocular Reflex in Unilateral Vestibular Neuritis: A Preliminary Study - Fu, Wei; He, Feng; Wei, Dong; Bai, Ya; Shi, Ying; Wang, Xiaoming; Han, Junliang (Frontiers in Neurology, 2019)
Objective: The aim of this preliminary study is to investigate the recovery pattern of the high-frequency acceleration vestibulo-ocular reflex(VOR) function of the horizontal semicircular canal in patients with unilateral vestibular neuritis (UVN). Methods: 47 consecutive patients with UVN were recruited within 10 days of symptom onset for this study. The high-frequency acceleration VOR function evaluation for horizontal semicircular canals was performed with video head impulse test (vHIT).Patients returned for follow-up evaluation at approximately 6 months after the onset of symptoms. According to the dizziness handicap inventory questionnaire(DHI), the patients were classified into the normal to mild dizziness group(DHI score≤30) and moderate to severe dizziness group (DHI score>30) at follow-up. All the obtained horizontal vHIT gains and corrective saccades parameters were analyzed. Results: vHIT results showed a significantly horizontal VOR gain recovery in UVN patients from the acute stage to the follow-up on the lesion side (p<0.01). A significantly reduction in the occurrence of corrective saccades(overt and covert) and velocity of corrective saccades(overt and covert) were observed from the acute stage to the follow-up (p<0.05). At the follow-up, the normal to mild dizziness patients(DHI score≤30) had a significantly higher normal rate of VOR gain, the mean vHIT gains and occurrence of isolated covert saccades (P<0.05). Furthermore, the occurrence of mixed saccades and the mean velocity of covert saccades were significantly lower in normal to mild dizziness patients (P<0.05). Conclusion: Apart from the recovery of the VOR gain, recovery pattern of corrective saccades can play a important role in vestibular compensate and improvement symptom.